Unique features of the mitochondrial rolling circle-plasmid mp1 from the higher plant Chenopodium album (L.) - Backert, Steffen; Meißner, Karsten; Börner, Thomas (Nucleic Acids Research, 1997)
We analyzed the structure and replication of the mitochondrial (mt) circular DNA plasmid mp1 (1309 bp) from the higher plant Chenopodium album (L.). Two dimensional gel electrophoresis (2DE) revealed the existence of oligomers of up to a decamer in addition to the prevailing monomeric form. The migration behavior of cut replication intermediates during 2DE was consistent with a rolling circle (RC) type of replication. We detected entirely single-stranded (ss) plasmid copies hybridizing only with one of the two DNA strands. This result indicates the occurence of an asymmetric RC replication mechanism. mp1 has, with respect to its replication, some unique features compared with bacterial RC plasmids. We identified and localized a strand-specific nicking site (origin of RC replication) on the plasmid by primer extension studies. Nicks in the plasmid were found to occur at any one of six nucleotides (TAAG/GG) around position 735 of the leading strand. This sequence shows no homology to origin motifs from known bacterial RC replicons. mp1 is the first described RC plasmid in a higher plant.
Created from Fastlane, Scopus look-up